Overview of KAGRA: Detector design and construction history. (17th August 2020) - Akutsu, T; Ando, M; Arai, K; Arai, Y; Araki, S; Araya, A; Aritomi, N; Aso, Y; Bae, S; Bae, Y; Baiotti, L; Bajpai, R; et al.
Abstract: KAGRA is a newly built gravitational-wave telescope, a laser interferometer comprising arms with a length of 3 km, located in Kamioka, Gifu, Japan. KAGRA was constructed under the ground and it is operated using cryogenic mirrors that help in reducing the seismic and thermal noise. Both technologies are expected to provide directions for the future of gravitational-wave telescopes. In 2019, KAGRA finished all installations with the designed configuration, which we call the baseline KAGRA . For this occasion, we present an overview of the baseline KAGRA from various viewpoints in a series of articles. In this article, we introduce the design configurations of KAGRA with its historical background.